Design enhancement of twin-tower seismic isolation structures with an enlarged basement through modal comparison - Hao, Cao (2025)
In recent years, seismic isolation, as an emerging technology, has found broader application in seismically active regions. However, most applications are limited to buildings with regular geometries, and few have been implemented in those complex structures like Twin-tower structures with an enlarged basement (2TSLB). Although some studies have investigated the seismic isolation techniques in 2TSLB structure, few studies have systematically compared the performance of inter-layer isolation and base isolation schemes. The limited findings are often inconsistent, leading to unclear conclusions. Furthermore, few studies have adopted the Structural Separation Design Method (SSDM) for this type of 2TSLB structure or considered the influence of its various height-to-width ratios on the selection of isolation schemes. Based on these research gaps, the main objective of this thesis is to investigate and compare the seismic isolation efficiency, safety performance and cost of 2TSLB structures with base isolation and interlayer isolation, while considering the influence of applying SSDM, various structural systems (including frame and shear-wall systems), and height-to-width ratios. This study developed twenty-three models compliant with the Chinese seismic codes, featuring different height-to-width ratios and structural systems, and performed comprehensive numerical analyses using ETABS on these models in three aspects: seismic isolation efficiency (e.g., in reducing internal forces and accelerations), safety (e.g., against collapse), and cost. The following main conclusions were drawn: 1) For such 2TSLB structures, generally, compared with base-isolated structures, inter-layer isolated structures exhibit superior safety performance (in terms of resisting collapse during earthquakes, qualified by metrics of the maximum earthquake acceleration that the structure can endure before failure) and lower construction costs. Nonetheless, the isolation efficiency (quantified by metrics such as largest maximum story shear force) of inter-layer isolated structure is relatively lower. 2) In the altered height-to-width ratio of the structure (from 4.16 to 2.38) and the structural system (from a shear-wall structure to a frame structure), these above conclusions remained consistent, thereby demonstrating the broad applicability of the findings. Subsequently, by combining these conclusions with practical experience, a decision process flow chart for seismic-isolated 2TSLB design was summarized. The conclusion of this study answers the questions raised by objectives, optimizes the structural design process, assists structural engineers quickly find the appropriate seismic isolation schemes, and provides additional theoretical basis for the application of isolation technology in complex structures such as 2TFSLB. It should be noted that this study is based on numerical analysis, and the findings could be further validated by experimental tests.